Forests and national security in Nigeria: an evaluation of the symboisis and challenges (2017)
Forests play many diverse and multifaceted roles in our life. However, there is an emerging nexus between forest and national security in many countries, especially within the sub-Saharan region of Africa. Contrary to the noble objectives for which they were constituted, many forest reserves have become a source of security concern both at the local and national scale. In the light of this, we examined the relationship between forest and national security in Nigeria, with a view to identifying how forests impact security situations and how security situations in turn impact forests, and what need to be done to mitigate the negative upshots along the continuum. It is noted that the management of forests and other protected areas in the country has been quite fortuitous. The laws and policies associated with forest and protected area management are obsolete while the supervision, monitoring and surveillance carried out in the forest areas leave much to be desired. Given the shared features between forest locations and the geography of violent conflicts, it is observed that forests can provide refuge, funds and food for insurgents and terrorists. In turn, armed conflicts and activities also negatively impact the forest through “ecocide” (the destruction of the environment by military operations), hunting wildlife for food, and setting of land mines that kill and maim many wildlife species. Against this backdrop, we conclude that, more than ever, forest reserves in Nigeria and elsewhere need adequate protection, effective legislations, proper staffing, regular assessment of the state and status of reserves, and restoring the requisite management activities in all reserves across the country.